Critical Thinking Skill And Independence on Learning Natural Science Based on Gender During The Covid-19 Pandemic - Ratna Wahyu Wulandari (STAI Hubbulwathan Duri, 2022)
To improve students' critical thinking skills, this study used online PBL (Problem-Based Learning) on learning Natural Science in the field of Biology. This research was conducted in pre-experimental research design with the subjects of 4th semester students in study program of PGMI (Teacher Education of Madrasah Ibtidaiyah). The results of the analysis showed that the improvement of critical thinking skill of female students is better than male groups. Based on the results of the hypothesis testing obtained from the data showed that the N_Gain critical thinking skill of male and female students were greater than α (sig. 0.051 ˃ (α) 0.05.), therefore H0 was accepted and H1 was rejected. That is, there is no difference in the improvement of critical thinking skill between male and female students. When it came from the indicators of critical thinking, the N-Gain score for all indicators of the female group was better than that of the male one. Also, for students’ independence, the average percentage of student responses in all aspects showed that they were in a Good category. The average percentage of student responses on the planning aspect was 73.65% in a Good category. The process aspect of student independent learning had the highest score among the three aspects, which was 75.73% or in the Good category, and the Learning Evaluation Aspect has the lowest score among the three aspects, which was 66.53% and was in a Good category.